How Politician Branded Themselves on Instagram : Ridwan Kamil's Case Study - Sya'ban, Muhammad Iqbal Rizqi; Windasari, Nila Armelia (Journal of Business and Management, 2020)
Abstract. There are more than 3 billion active social media users in the world. With 1 billion unique users, Instagram is renowned as the fastest growing social media. Not only used for social purposes, but also for political tool amongst politicians. In this case, Ridwan Kamil, the current governor of west java, is one of them. By being the 2 nd most followed politician on Instagram with 11 million followers. This research aims to analyze Ridwan Kamil Instagram on how he potrayed himself on social media. This research uses content analysis and sentiment analysis with TF-IDF (Term Frequency – Inverse Document Frequency) method. We analyze 70 posts that derived into ten categories. The result has shown that Family-related posts were getting the highest average engagement rate (1.739%), followed by Humour-related posts (1.617%); these two categories often reciprocates. Ridwan Kamil frequently includes himself with 55.71% appearance out of all posts, followed by his Family. Based on the Sentiment Analysis, Ridwan Kamil gets mostly positive sentiments (95.7%). There is a strong correlation between the posts gap of each category and the average engagement. It has reversive correlation which we believe that Ridwan Kamil still needs to portray himself as 'professional' and expert in his field, while still connected personally by personal posts to perceive himself as a part of the community. The findings of this research are expected to give insights to politicians and marketers in formulating their social media presence in the digital era.Keywords: Instagram, Politician, Ridwan Kamil, Content Analysis, Sentiment Analysis